Optimized surface treatment of aerospace composites using a picosecond laser. (15th October 2019) - Palmieri, Frank L.; Ledesma, Rodolfo I.; Dennie, Joseph G.; Kramer, Teersa J.; Lin, Yi; Hopkins, John W.; Wohl, Christopher J.; Connell, John W.
Abstract: In this work, a design of experiments (DoE) approach was used to determine optimum laser surface treatment conditions. Aerospace structural carbon fiber reinforced composites (Torayca® T800H/3900-2) were laser treated using a pulsed laser source with a wavelength of 355 nm, nominal pulse width of 10 ps, average power up to 7 W, and spot size of approximately 20 μm. The laser power, frequency, scan speed, and number of passes (1 or 2) were varied. The adherends were characterized using a handheld water contact angle device, scanning electron microscopy (SEM), optical profilometry, and laser induced breakdown spectroscopy (LIBS). Bonded specimens were mechanically tested using a modified double cantilever beam (DCB) method. The response models obtained from the DoE indicated that surface characteristics of adherends and failure modes of bonds were most sensitive to the average laser power. Below about 200 mW, adhesive failure was observed. For laser powers greater than about 600 mW, surface resin was largely removed from the fiber bed, and the failure mode was predominantly fiber tear. Cohesive failure (∼100%) was observed for a wide range of laser parameters indicating that laser treatment can be a robust means of surface preparation.